1993
DOI: 10.1111/j.1432-1033.1993.tb18197.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of human milk fucosyltransferase in the synthesis of tumor‐associated trimeric X determinants

Abstract: We have studied the fucosylation of a chemically synthesized trimer of N-acetyllactosamine [(LacNAc),-EtPhNHCOCF,] with a fucosyltransferase preparation from normal human milk, which utilizes both type-1 and type-2 structures, whether sialylated or not. When fucose residues were added enzymically to the (LacNAc),-EtPhNHCOCF, hexasaccharide, mono-, di-, or trifucosylated oligosaccharide species were formed, containing the LewisX determinant (Gal~l+4[Fucal+3]GlcNAcPl-3). With excess GDP-fucose and prolonged reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 46 publications
(14 reference statements)
1
24
0
Order By: Relevance
“…Functionally purified preparations of human milk ~3/4-fucosyltransferase have been used in the enzyme assisted synthesis of ~(1 3)-fucosylated oligosaccharides, including Le x [7][8][9]12]. Here it is demonstrated that the enzyme can also be used to produce the GalNAc-containing variant of Le x in high yield.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functionally purified preparations of human milk ~3/4-fucosyltransferase have been used in the enzyme assisted synthesis of ~(1 3)-fucosylated oligosaccharides, including Le x [7][8][9]12]. Here it is demonstrated that the enzyme can also be used to produce the GalNAc-containing variant of Le x in high yield.…”
Section: Discussionmentioning
confidence: 99%
“…GDP-[3H]Fuc (7 Ci/mmol) was purchased from DuPont NEN (Boston, MA), and was diluted with unlabelled GDP-Fuc. Partially purified human milk c~3/4-fucosyltransferase, kindly provided by Mrs. T. De Vries, was isolated from pooled human milk as described in [11] with minor modifications [12]. The resulting preparation contained the enzyme in a 225-fold purified form (1.4 mU/ml) in a solution of 50 mM sodium cacodylate buffer, pH 7.2, containing 50% (by vol.)…”
Section: Methodsmentioning
confidence: 99%
“…Five micromoles of GlcNAc-R was incubated with 6 µmol of UDP-[ 3 H]GalNAc (0.09 Ci/mol) and partially purified UDP-GalNAc:GlcNAcβ β1→4-N-acetylgalactosaminyltransferase (β4-GalNAcT) from the albumen gland of Lymnea stagnalis (Mulder et al, 1995) in an incubation mixture containing 100 mM sodium cacodylate pH 6.5, 20 mM MnCl 2 , 100 mM NaCl, 600 mM GlcNAc, 4 mM ATP, and 0.5% (v/v) Triton X-100 for 18 h at 37°C. Three micromoles of the produced LacdiNAc-R was fucosylated with 4 µmol of GDPFuc and partially purified GDP-Fuc:[Galβ1→4]GlcNAcβ α1→3-fucosyltransferase (α3-FucT) (1.4 mU) from human milk (DeVries et al, 1993) in an incubation mixture containing 100 mM sodium cacodylate pH 7.0, 100 mM NaCl, 20 mM MnCl 2 , 4 mM ATP and 0.5% (v/v) Triton X-100, for 48 h at 37°C (Bergwerff et al, 1993). Two µmol of LDN-F was further fucosylated with partially purified GDP-Fuc:Fucα α1→2-fucosyltransferase (α2-FucT) from T.ocellata (Hokke et al, 1998) under the same conditions as described previously, for 72 h at 24°C.…”
Section: Enzymatic Synthesis Of Oligosaccharidesmentioning
confidence: 99%
“…For instance, endo-β-galactosidase of B.fragilis, cleaving internal β-galactosidic bonds of primary polylactosamine backbones, does not hydrolyze these bonds in LacNAc units that are α1, 3-fucosylated (de Vries et al, 1993), β1,6′-N-acetylglucosaminylated (Scudder et al, 1984), or 6′-sulfated (Scudder et al, 1983). Analogous examples also include α1,3-fucosyltransferases, which transfer to all LacNAc units of linear polylactosamine chains (de Vries et al, 1993;Niemelä et al, 1998), but work poorly at branch-bearing LacNAc units .…”
Section: Introductionmentioning
confidence: 99%